Business challenges and strategies in Brazil's infrastructure-deficient market: case study over the logistic performances - Scotto, Massimo (2024)
The general status of logistic infrastructure highly affects the normal cycle of business operations in an economy, for emerging markets the constrains shape the development of optimal or suboptimal equilibria and practices as far as concern the distributional choices and production strategies to fit the market conditions or specific regulations and standard. The case study here presented would like to examinate the current organizational set up and strategies adopted by a company operating in Brazil relative to the analysis of the domestic and regional market. The interviews and the financial analysis provided have been crucial to understand the real hurdles faced by the company that combines a difficult institutional and logistic set up with an internal problem of cost identification relative to the procurement. The analysis compared the transportations costs of the group, a multinational company, Mattapelli S.p.A, with the ones of the Brazilian subsidiary to understand if, and in which magnitude, the environmental factors create or not a cost difference among the averages. The international means of comparison arising form two other developing markets, Nigeria and Malaysia, are a benchmark and an insight to understand some common features relative to the hedging strategies adopted by various firms operating in different developing economies.